Correlation between Skeletal Malocclusion and the Dimensions of Maxillary and Frontal Sinuses using Lateral Cephalograms: A Cross-sectional Study - Shiladitya Sil; Kerthna Selvan; Nilanjana Saha; Subhankar Ghosh (Journal of Clinical and Diagnostic Research, 2023)
Introduction: Lateral cephalograms are routinely used in orthodontics for accurate assessment and treatment planning of malocclusion. Paranasal air sinuses, such as the maxillary and frontal sinuses, are visible in the lateral cephalogram. However, a direct correlation between the area of these sinuses and the tendency to develop skeletal discrepancies has not been studied in the literature. Aim: To determine the cephalometric correlation between different skeletal malocclusions and the dimensions of the frontal and maxillary sinuses. Materials and Methods: A cross-sectional cephalometric study was conducted at a Tertiary Care Centre in Siliguri district of West Bengal, India. The duration of the study was two years, from August 2019 to September 2021. A total of 150 patients were included and they were divided into three equal groups: skeletal class I (n=50), skeletal class II (n=50), and skeletal class III (n=50). Multiple cephalometric parameters were traced on the radiographs using Dolphin and AutoCAD software, and they were compared among the three groups. The data were analysed using Pearson’s correlation test. Results: The results showed a statistically significant correlation between Maxillary Sinus Area (MSA) and Gonial angle (r=0.468, p=0.001) in skeletal class I malocclusion. In skeletal class II malocclusion, a significant negative correlation was found between Frontal Sinus Area (FSA) and total mandibular length (r=-0.30, p=0.009). However, no significant negative correlation was found between MSA and any cephalometric parameter in skeletal class II malocclusion. Conclusion: The present study highlights there was an increase in the size of the maxillary and frontal sinuses was observed in skeletal class II and skeletal class III malocclusion. However, no correlation could be found between skeletal class I malocclusion and the areas of the frontal sinus.